The behavioural learning classroom making schools more effective and compassionate - Mallard, Graham 1982- (Abingdon, Oxon Routledge, Taylor & Francis Group, 2023)
"Teachers are virtually never taught how learners make decisions about studying, concentration and participation, and are not able to find this in education literature. The Behavioural Learning Classroom breaks new ground, allowing teachers to harness their students' traits and quirks to produce a more effective and compassionate classroom. Important lessons from behavioural science Optimising lesson design Effective (home)work Marking and feedback The physical environment of the classroom Pupil behaviour Designing behavioural experiments and analysing data Supported by fundamental findings in behavioural science, this book provides practical, accessible, tried and tested techniques to improve the mental wellbeing of pupils and teachers alike. It is an enjoyable and accessible read for any teacher or school leader who wants to enhance their pupils' experience of learning"--
Section 1. Learning -- Section 2. Behaviour -- Section 3. Wider Issues.
Includes bibliographical references and index.
Keywords: Behavioral assessment of children; Classroom environment; Effective teaching; Interpersonal communication; Teacher-student relationships